A conserved E3 ubiquitin ligase rewires carotenoid, sterol, and lipid metabolism in Xanthophyllomyces dendrorhous - Ruilin Huang; Jiurong Wang; Ruirui Ding; Yu Liu; Juanjuan Su; Zhihang Chen; Yong Fan; Fuli Li; Linqi Wang; Xiao Liu; Shi’an Wang (Proceedings of the National Academy of Sciences, 2026)
Sterols, lipids, and carotenoids are major metabolites that share common biosynthetic precursors and underpin key physiological processes in eukaryotes. Yet, how cells coordinate metabolic flux through these competing pathways to maintain homeostasis remains unclear. Here, we identify a conserved RING-type E3 ubiquitin ligase, PTR1, as a central regulatory hub that orchestrates the interplay among these pathways in the yeast Xanthophyllomyces dendrorhous . Disruption of PTR1 triggers a concerted metabolic rewiring that enhances astaxanthin and sterol biosynthesis while shifting fatty acid composition toward polyunsaturation. Integrated multiomics and protein interaction analyses suggest that PTR1 targets White Collar 1 (WC1) for ubiquitination, establishing a reciprocal regulatory loop that maintains carotenoid homeostasis. Beyond WC1, PTR1 interfaces with a broader metabolic network to fine-tune central metabolism through discrete regulatory nodes. Notably, PTR1 homologs are found across evolutionarily distant eukaryotic lineages, including fungi, algae, plants, and animals, highlighting deep evolutionary conservation of the underlying protein architecture. These findings uncover a mechanism by which protein ubiquitination contributes to the coordination of distinct yet interconnected biosynthetic pathways in X. dendrorhous and point to the potential broader relevance of ubiquitin-mediated metabolic coordination beyond this species.